Relevance theory, figuration, and continuity in pragmatics - Piskorska, Agnieszka (Figurative thought and language ;, 2020)
"The chapters in this volume apply the methodology of relevance theory to develop accounts of various pragmatic phenomena which can be associated with the broadly conceived notion of style. Some of them are devoted to central cases of figurative language (metaphor, metonymy, puns, irony) while others deal with issues not readily associated with figurativeness (from multimodal communicative stimuli through strong and weak implicatures to discourse functions of connectives, particles and participles). Other chapters shed light on the use of specific communicative styles, ranging from hate speech to humour and humorous irony. Using the relevance-theoretic toolkit to analyse a spectrum of style-related issues, this volume makes a case for the model of pragmatics founded upon inference and continuity, understood as the non-existence of sharply delineated boundaries between classes of communicative phenomena"--